The Impact of ESG Ratings on Exchange-Traded Fund Flows - Yuri Dranev; Mikhail Miriakov; Elena Ochirova; Gennadii Baranovskii (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2024)
The aim of our paper is to examine the impact of environmental, social, and governance (ESG) ratings on investment decisions in the pre-pandemic US bond and equity exchange-traded fund (ETF) markets. We measure the attractiveness of investments in the ETF as net fund flows and estimate whether the attractiveness varies with the ESG score. For empirical estimations, we employ the regression analysis methodology; specifically, we use linear mixed-effect model to analyze time-series dataset and ordinary least squares to analyze the cross-section data. On the one hand, we found that, on average, ETFs which comply with ESG criteria attracted additional net assets per month as compared to conventional ETFs. Thus,the results of our study indicate that investors demonstrate collective preference towards ESG investments and pay attention to the information on whether the ETF complies with the ESG criteria. On the other hand, we found mixed evidence that higher ESG score always leads to larger investments: differences in scores could not explain the variation in net fund flows. Overall, our study shows that ETF market investments are not directed by the risk-return profile only, and investors also have non-pecuniary motives for their decisions. The results have several practical implications. First, our findings offer business entities useful insight into the fact that incorporation of ESG policy can increase the attractiveness of their business for potential investors. Second, it shows that the market participants would benefit from increasing transparency and unification of rating methodology.